Re-identifying Muslimah Identity in Sabeeha Rehman’s Threading My Prayer Rug - Bhagat, Diksha; Vohra, Anupama (Muslim English Literature, 2024)
Diaspora denotes people or a group of people who have been separated from their homeland and are resettled in a foreign land. Migration is a complex process; it is of different types depending on whether it is voluntary or forced due to enslavement, war, famine, or some other natural or man-made disaster. Globalization has influenced and increased the prospect of migration all over the world. As a result, people are more open to migrating to different corners of the world, especially for work and a better lifestyle. Against this background, the paper deals with migration and the resultant diaspora experienced by Sabeeha Rehman, a Muslim migrant woman from Pakistan to America. Her memoir, Threading My Prayer Rug: One Woman’s Journey from Pakistani Muslim to American Muslim (2016), deals with the struggles of Muslim women‘s confrontation and assimilation into a completely alien democratic environment of the West where the followers of different faiths exist simultaneously. Thus, this paper highlights the various experiences Sabeeha faces as a Muslimah or Muslim woman on religious and cultural fronts and her constant battle to retain her religious identity in a non-Muslim (dar ul-harb) country.